Blind subjects construct conscious mental images of visual scenes encoded in musical form - Cronly-Dillon, J.; Persaud, K. C.; Blore, R. (Proceedings of the Royal Society. B, Biological sciences, 2000)
Blind (previously sighted) subjects are able to analyse, describe and graphically represent a number of high-contrast visual images translated into musical form de novo. We presented musical transforms of a random assortment of photographic images of objects and urban scenes to such subjects, a few of which depicted architectural and other landmarks that may be useful in navigating a route to a particular destination. Our blind subjects were able to use the sound representation to construct a conscious mental image that was revealed by their ability to depict a visual target by drawing it. We noted the similarity between the way the visual system integrates information from successive fixations to form a representation that is stable across eye movements and the way a succession of image frames (encoded in sound) which depict different portions of the image are integrated to form a seamless mental image. Finally, we discuss the profound resemblance between the way a professional musician carries out a structural analysis of a musical composition in order to relate its structure to the perception of musical form and the strategies used by our blind subjects in isolating structural features that collectively reveal the identity of visual form.